?????????? ?????????????? ???? ???????????? ?????????????????? - Agus Aulia Elluthfi (Lughoti (Jurnal Pendidikan Bahasa Arab) Jurnal program studi PBA, 2022)
Arabic is one of the most unique and influencing language in civilization and history of nations. Turkey is one of nation significantly influenced by Arabic. This research try to undertake the influence of Arabic in the history of Turkish Civilization. This research used Descriptive-Analitic method. The results of this research proofed that untill the 8th century of Hijriya, the Ottomans was familiar with Arabic. In that time, Arabic was integrated in their activities such as prayers, education, and scientific papers. Majority of Ottoman Empire Sultans were able to speak Arabic. Infact, there were some Sultans that made poems and prose including Sultan Selim I (1520), Sultan Ahmad I (1617), Sultan Abdul Hamid Khan (1918), etc. The influence of Arabic in the civilization of Ottoman Empire was also seen in the sentences and terms of Turkish. It is recorded that 70% of words in Turkish were rooted from Arabic.